2019
DOI: 10.1111/asj.13213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the stems and leaves of Astragalus membranaceus on growth performance, immunological parameters, antioxidant status, and intestinal bacteria of quail

Abstract: This study was designed to evaluate the potential application of the stems and leaves of Astragalus membranaceus (AMSL) in the poultry industry. Quails were divided into four groups and fed daily with an AMSL‐free diet (control) or with 1%, 3%, or 5% (w/w) AMSL‐incorporated diets for 35 days. The results showed that supplementing AMSL in the diet, especially at a concentration of 3%, increased daily gain and feed intake during the entire experiment (p < 0.05). The immune organ development of the thymus and bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Its root contains polysaccharides, which increased serum antibodies, cytokines and antioxidants in mice [ 4 ]. In addition, its leaves promoted intestinal proliferation of lactic acid bacteria and inhibited the growth of coliform bacteria in quail [ 5 ]. In a companion paper [ 6 ], supplementary A. membranaceus improved average daily gain, rumen fermentation, and serum antioxidant capacity and immunity indices of Tibetan sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Its root contains polysaccharides, which increased serum antibodies, cytokines and antioxidants in mice [ 4 ]. In addition, its leaves promoted intestinal proliferation of lactic acid bacteria and inhibited the growth of coliform bacteria in quail [ 5 ]. In a companion paper [ 6 ], supplementary A. membranaceus improved average daily gain, rumen fermentation, and serum antioxidant capacity and immunity indices of Tibetan sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations have shown that the main active constituents of Astragali Radix include flavonoids, astragalosides, polysaccharides, amino acids, nucleotides and some trance elements 5–8 . Pharmacological and preclinical studies have revealed that Astragali Radix has diverse bioactivities, such as antioxidant, anticancer, anti‐inflammatory, and immune‐regulatory 5,9,10 . Among these, the antioxidant capacity is one of its most important pharmaceutical effects as it can facilitate the prevention of oxidative damage caused by free radicals, leading to ageing, cancer, and cardiovascular and neurodegenerative diseases 11 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Pharmacological and preclinical studies have revealed that Astragali Radix has diverse bioactivities, such as antioxidant, anticancer, anti-inflammatory, and immune-regulatory. 5,9,10 Among these, the antioxidant capacity is one of its most important pharmaceutical effects as it can facilitate the prevention of oxidative damage caused by free radicals, leading to ageing, cancer, and cardiovascular and neurodegenerative diseases. 11 Astragali Radix is widely distributed in northern China, across the east-west region of up to 5200 km, wherein the Shanxi, Gansu, and Inner Mongolia provinces are the predominant producers.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of studies supports the use of herbal medicines, herbal formulas, and phytochemicals, such as Gegen Qinlian Decoction formula, Qushi Huayu Decotion formula, and quercetin, which could upregulate the beneficial gut microbiota ( Meng et al., 2018 ). Feeding incorporated diets with appropriate A. membranaceus regulated the intestinal flora by promoting the proliferation of Lactobacillus and inhibiting the growth of coliform bacteria ( Guo et al., 2019 ). Probiotics combined with Astragalus polysaccharide administration in feed displayed synergistic modulation effects on intestinal microbiota ( Li et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%